Implementation science in adolescent healthcare research: an integrative review - Elham Zolfaghari; Natasha Armaghanian; Daniel Waller; Sharon Medlow; Annabelle Hobbs; Lin Perry; Katie Nguyen; Katharine Steinbeck (BMC, 2022)
Abstract Background Multiple theories, models and frameworks have been developed to assist implementation of evidence-based practice. However, to date there has been no review of implementation literature specific to adolescent healthcare. This integrative review therefore aimed to determine what implementation science theories, models and frameworks have been applied, what elements of these frameworks have been identified as influential in promoting the implementation and sustainability of service intervention, and to what extent, in what capacity and at what time points has the contribution of adolescent consumer perspectives on evidence implementation been considered.  Methods An integrative design was used and reported based on a modified form of the PRISMA (2020) checklist. Seven databases were searched for English language primary research which included any implementation science theory, model or framework developed for/with adolescents or applied in relation to adolescent healthcare services within the past 10 years. Content and thematic analysis were applied with the Consolidated Framework for Implementation Research (CFIR) used to frame analysis of the barriers and facilitators to effective implementation of evidence-informed interventions within youth health settings. Results From 8717 citations, 13 papers reporting 12 studies were retained. Nine different implementation science theories, frameworks or approaches were applied; six of 12 studies used the CFIR, solely or with other models. All CFIR domains were represented as facilitators and barriers for implementation in included studies. However, there was little or no inclusion of adolescents in the development or review of these initiatives. Only three mentioned youth input, occurring in the pre-implementation or implementation stages. Conclusions The few studies found for this review highlight the internationally under-developed nature of this topic. Flagging the importance of the unique characteristics of this particular age group, and of the interventions and strategies to target it, the minimal input of adolescent consumers is cause for concern. Further research is clearly needed and must ensure that youth consumers are engaged from the start and consistently throughout; that their voice is prioritised and not tokenistic; that their contribution is taken seriously. Only then will age-appropriate evidence implementation enable innovations in youth health services to achieve the evidence-based outcomes they offer. Trial Registration PROSPERO 2020 CRD42020201142 https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=201142